ENGEMBANGAN MEDIA AUGMENTED REALITY PADA MATERI SEGI EMPAT KELAS IV SEKOLAH DASAR - Wika Fauzi; Vivi Puspita; Sri Apfani (Jurnal Riset Pendidikan Dasar Dan Karakter, 2025)
The integration of information and communication technology in 21st-century education has become essential to improve the quality of learning. This study aimed to develop an Augmented Reality (AR)-based learning media using the Assemblr Edu application for quadrilateral topics in fourth-grade elementary school that is valid, practical, and effective. This research employed a Research and Development (R&D) approach using the ADDIE development model, which consists of the stages of analysis, design, development, implementation, and evaluation. The product was validated by experts in media, content, and language. Practicality was assessed through questionnaires completed by teachers and students, while effectiveness was measured using objective and essay evaluation tests. The results showed a validity score of 81.66% (valid), practicality scores of 94.28% and 91.2% (very practical), and an effectiveness score of 92.3% (very effective). Therefore, the developed AR-based learning media is considered feasible for teaching quadrilateral material in fourth-grade elementary school.